2017
DOI: 10.1186/s13045-017-0459-2
|View full text |Cite
|
Sign up to set email alerts
|

Vaccination with poly(IC:LC) and peptide-pulsed autologous dendritic cells in patients with pancreatic cancer

Abstract: BackgroundDendritic cells (DCs) enhance the quality of anti-tumor immune response in patients with cancer. Thus, we posit that DC-based immunotherapy, in conjunction with toll-like receptor (TLR)-3 agonist poly-ICLC, is a promising approach for harnessing immunity against metastatic or locally advanced unresectable pancreatic cancer (PC).MethodsWe generated autologous DCs from the peripheral blood of HLA-A2+ patients with PC. DCs were pulsed with three distinct A2-restricted peptides: 1) human telomerase rever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
91
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 118 publications
(97 citation statements)
references
References 68 publications
2
91
0
4
Order By: Relevance
“…In one of our recent studies, we used the clinical grade (Hiltonol®) of poly(I:C) in a clinical trial of pancreatic cancer to enhance vaccination with DCs loaded with tumour peptides [51]. Hiltonol® was used for the purpose to activate DCs in vitro before loading the peptides as well as in vivo by its administration along with DC vaccine at the vaccination site.…”
Section: Discussionmentioning
confidence: 99%
“…In one of our recent studies, we used the clinical grade (Hiltonol®) of poly(I:C) in a clinical trial of pancreatic cancer to enhance vaccination with DCs loaded with tumour peptides [51]. Hiltonol® was used for the purpose to activate DCs in vitro before loading the peptides as well as in vivo by its administration along with DC vaccine at the vaccination site.…”
Section: Discussionmentioning
confidence: 99%
“…A more stable derivative, poly(IC:LC), obtained by modification with poly-L-lysine and carboxymethyl cellulose, has been successfully used in mice for prophylactic and therapeutic protection against a broad spectrum of human viruses including lethal severe acute respiratory syndrome coronavirus (SARS-CoV), lethal H5N1 IAV, and RSV (Table 1) [63][64][65][66]. Incorporating poly(IC:LC) as adjuvant also enhanced the clinical efficiency of experimental vaccines in patients with recurrent malignant glioma, ovarian cancer, or pancreatic cancer [67][68][69]. The undefined structure, heterogeneity, and polydispersity of HMW poly(I:C) and analogs together with unpredictable pharmacokinetics and toxicity, present a hurdle for therapeutic use [4].…”
Section: Targeting Rlrs For Therapeutic and Prophylactic Strategiesmentioning
confidence: 99%
“…Less than two decades after the first reports characterizing the role of RLRs in immunity, we are closer than ever to having RLR ligands in clinical applications. Pilot trial and ongoing clinical trials in humans are yielding promising results, notably for cancer immunotherapy [67][68][69]85]. Although we have come a long way and key milestones have been reached, there are still significant knowledge gaps that need to be filled by use of molecular, cellular, and structural biology approaches to not only be able to design exclusive and potent RIG-I or MDA5 ligands but also to decide on the most appropriate target for use in antiviral, vaccine adjuvant, or cancer immunotherapeutic applications (see Outstanding Questions).…”
Section: Concluding Remarks and Future Perspectivesmentioning
confidence: 99%
“…Studies of biological properties of PolyI: PolyC, started in the 1970s, showed that the drug was a powerful activator of innate immunity and an inducer of tumor cell apoptosis [44]. Promising results have been obtained in clinical studies of PolyI:PolyC as a means of treating seasonal influenza [71], as well as treating malignant tumors of different localizations in adults and children [72][73][74].…”
Section: Virusinfected Cellsmentioning
confidence: 99%